Improvement of intestinal peptide absorption by a synthetic bile acid derivative, cholylsarcosine - Michael, Susanne; Thöle, Marc; Dillmann-Marschner, Ruth; Fricker, Gert (European journal of pharmaceutical sciences, 2000)
The potential of the nontoxic bile salt derivative, cholylsarcosine, to enhance the intestinal absorption of peptides was investigated in vitro and in situ. The permeation of the two model peptides octreotide and vasopressin-[arg8] (desmopressin) and the paracellular marker FITC-Dextran 4000 across Caco-2 cell (originally derived from a human colorectal carcinoma) monolayers was studied in the absence and in the presence of bile acids, including cholylsarcosine (CS). The absorption of the peptides was also determined in situ in rats. The absolute absorption efficiency was calculated by determination of plasma levels after intravenous administration of the peptides. Cytotoxic properties of the bile acids were studied using the following assays: WST-1-transformation measuring mitochondrial dehydrogenase activity as an indicator of cell proliferation and cell viability, lactate dehydrogenase (LDH) release by the Caco-2 cells and assessment of the transepithelial electrical resistance. CS, cholyltaurine (CT) and chenodeoxycholic acid (CDCA) showed an enhancing effect on peptide permeation across Caco-2 cell monolayers with the rank order CDCA>CT≥CS, whereas ursodeoxycholic acid exhibited no absorption enhancement. Determination of the cytotoxic potential of the bile salts revealed the same rank order. In rats, octreotide and desmopressin were absorbed from the gastrointestinal-tract with moderate absorption efficiency. Coadministration of bile salts resulted in an increased absorption efficiency. The effect of CS was similar to that of CT. In conclusion, CS shows absorption enhancement properties and a relatively low cytotoxicity. It offers an alternative as absorption enhancer as compared to conventional bile acids which may have a potential cocarcinogenic risk.
Gesehen am 26.04.2017